RANCANG BANGUN PENGENDALI SEPEDA AIR BERBASIS MOTOR BLDC SEBAGAI SARANA WISATA DI DESA BUDO - Moha, Uviansyah; Lasik, Kesya K; Lintjewas, Angreyni J; Sawidin, Sukandar; Kantohe, Doostenreyk Kantohe (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Budo Village has significant potential for water tourism; however, the utilization of environmentally friendly recreational facilities remains limited, thereby requiring technological innovation to enhance tourist attraction. This study aims to design a BLDC (Brushless Direct Current) motor-based water bicycle control system that is reliable, safe, and efficient as a supporting tourism facility. The research employed an engineering design method by integrating a two-channel 2.4 GHz FlySky GT2 transmitter and a three-channel GR3E receiver as the wireless control system. The mechanical propulsion system combines a 36V/500W BLDC motor with a 7-inch three-blade propeller connected through a flexible coupling and a stainless steel shaft. Speed regulation is controlled using a 40A waterproof ESC, while steering control is operated by a DS3225 servo. The entire electrical system is powered by a 36V/25Ah LiFePO4 battery housed in a control enclosure designed to meet IP67 characteristics. The results indicate that the proposed control system design is theoretically capable of supporting responsive remote control operation, protecting electrical components from water-environment exposure, and maintaining propulsion system stability for water tourism vehicle operation. Therefore, this design has the potential to be further developed as a supporting tourism facility in Budo Village.